2019
DOI: 10.1021/acs.jproteome.9b00440
|View full text |Cite
|
Sign up to set email alerts
|

UPLC–QTOF-MS-Based Plasma Lipidomic Profiling Reveals Biomarkers for Inflammatory Bowel Disease Diagnosis

Abstract: Identification of new biomarkers may help in the early diagnosis of inflammatory bowel disease (IBD). In this study, ultrahigh-performance liquid chromatography equipped with quadrupole time-of-flight mass spectrometry (UPLC−QTOF-MS) was used to analyze the untargeted lipidomics and compare plasma lipid profiles between IBD patients and control subjects. The principal component analysis and partial least-squares-discriminant analysis were carried out to distinguish IBD patients from control subjects. Using uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 49 publications
4
41
0
Order By: Relevance
“…Certain studies focused specifically on the involvement of SLs in IBD. The roles of ceramide (Cer), ceramide-1-phosphate (C1P), sphingomyelin (SM; Sph), and sphingoid-1-phosphate (S1P) in IBD development were examined (Guan et al, 2020 PC 10:0/26:2, PC 12:0/22:2, PC 12:0/24:2, PC 14:1/22:4, PC 16:1/16:0, PC 14:0/14:0, PC 14:0/16:0, PC 16:0/18:1, PC 18:1/18:0 Another study focusing on UC proposed that SLs may serve as key immunomodulators. However, this report was excluded from our review as the analyses therein were conducted on mice rather than humans.…”
Section: Slsmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain studies focused specifically on the involvement of SLs in IBD. The roles of ceramide (Cer), ceramide-1-phosphate (C1P), sphingomyelin (SM; Sph), and sphingoid-1-phosphate (S1P) in IBD development were examined (Guan et al, 2020 PC 10:0/26:2, PC 12:0/22:2, PC 12:0/24:2, PC 14:1/22:4, PC 16:1/16:0, PC 14:0/14:0, PC 14:0/16:0, PC 16:0/18:1, PC 18:1/18:0 Another study focusing on UC proposed that SLs may serve as key immunomodulators. However, this report was excluded from our review as the analyses therein were conducted on mice rather than humans.…”
Section: Slsmentioning
confidence: 99%
“…For all reports except one, patients were categorized as CD or UC based on clinical and histological criteria. In the other study, the experimental group comprised all patients with CD and UC and they were collectively compared against healthy controls ( Guan et al ., 2020 ). In eight studies, CD and UC patients were individually compared with healthy controls.…”
Section: Analysis and Presentation Of Extracted Datamentioning
confidence: 99%
“…Logistic regression analysis, ANOVA statistics, and an ensemble approach with random sub-sampling have been widely used to select important features [ 37 39 ]. Another way to reduce the dimension of potential features is using unsupervised-machine learning, such as least absolute shrinkage and selection operator (LASSO) regression or principal component analysis (PCA) [ 40 ]. LASSO regression, one approach of regression analysis, has the feature of part of the coefficient being set to zero, reducing that dimension of the feature.…”
Section: Ai In Medicine—concepts and Utilizationmentioning
confidence: 99%
“…Meanwhile, PCA weighs and integrates many features to create a relatively small number of new features that represent the overall variability. Guan et al performed PCA to distinguish patients with inflammatory bowel disease (IBD) from control subjects using 55 lipid species [ 40 ]. They defined two new features of principal component 1(PC1) and principal component 2 (PC2), which were able to distinguish between patients with IBD and the control subjects.…”
Section: Ai In Medicine—concepts and Utilizationmentioning
confidence: 99%
“…Metabolomics is a comprehensive study of the types, quantities, and changes of endogenous metabolites under the influence of internal and external factors (such as pathological stimuli and drug intervention) on organisms [10]. Nontargeted metabolomics is the unbiased detection of the dynamic changes of all small molecule metabolites in biological samples, screening for potential biomarkers, and explaining molecular mechanisms [11]. More and more studies have shown that the gut microbiota and its metabolites are closely related to chronic heart failure [12].…”
Section: Introductionmentioning
confidence: 99%